2008
DOI: 10.1007/s10936-008-9069-z
|View full text |Cite
|
Sign up to set email alerts
|

What Do Second Language Listeners Know About Spoken Words? Effects of Experience and Attention in Spoken Word Processing

Abstract: With a goal of investigating psycholinguistic bases of spoken word processing in a second language (L2), this study examined L2 learners' sensitivity to phonological information in spoken L2 words as a function of their L2 experience and attentional demands of a learning task. Fifty-two Chinese learners of English who differed in amount of L2 experience (longer vs. shorter residence in L2 environment) were tested in an auditory word priming experiment on well-known L2 words under two processing orientation con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…This would also be in line with a higher sensitivity to acoustic patterns in the speech signal by listeners with a higher lexical proficiency, who are, as a consequence, better at encoding indexical information and consequently better at discriminating familiar and unfamiliar talkers. A similar explanation was offered by Trofimovich (2008) who suggested that more experienced non-native listeners are likely to be better at encoding context-specific phonological information from non-native words, and thus have an improved encoding of indexical information and discrimination of familiar and unfamiliar talkers.…”
Section: The Effect Of Background Noise and Lexical Proficiency On Thmentioning
confidence: 58%
See 2 more Smart Citations
“…This would also be in line with a higher sensitivity to acoustic patterns in the speech signal by listeners with a higher lexical proficiency, who are, as a consequence, better at encoding indexical information and consequently better at discriminating familiar and unfamiliar talkers. A similar explanation was offered by Trofimovich (2008) who suggested that more experienced non-native listeners are likely to be better at encoding context-specific phonological information from non-native words, and thus have an improved encoding of indexical information and discrimination of familiar and unfamiliar talkers.…”
Section: The Effect Of Background Noise and Lexical Proficiency On Thmentioning
confidence: 58%
“…The presence of background noise slows down the speech recognition process (Brouwer & Bradlow, 2011 dependent on the listeners' amount of experience with the non-native language (Trofimovich, 2008). Trofimovich (2008) argued that more experienced listeners were more sensitive to phonetic detail in spoken words in the non-native language, and therefore, experienced more facilitation from the same talker than the listeners with less experience in the non-native language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implicit learning occurs because the phonetic/phonological information contained in spoken words is encoded and stored in listeners' implicit memory, facilitating subsequent speech processing. Previous studies have revealed that just one instance of hearing of a word can facilitate subsequent speech perception of the word (e.g., Hori & Sugiura, 2013;Sugiura & Hori, 2012;Trofimovich, 2005;Trofimovich, 2008;Trofimovich & Gatbonton, 2006). Since there is a strong relationship between speech perception and production (Galantucci, Fowler, & Turvey, 2006) in speech acquisition, increased repetition of presented auditory words can raise learners' sensitivity to phonetic/phonological information in L2 auditory input, and this greater sensitivity is expected to promote pronunciation accuracy as well.…”
Section: Auditory Word Repetitionmentioning
confidence: 99%
“…Conversely, early-stage L2 learners find it harder to recognise the words comprising L2 speech (Goh, 2000). This difficulty stems from the intrinsically blended and ephemeral nature of the speech signal in addition to the learner's relative paucity of exposure to contextualised examples of the target language in the aural modality (Hulstijn, 2003;Trofimovich, 2008). Consequently, L2 listeners are often unable to adequately process the incoming L2 speech signal, relying strongly on guessing and contextual cues as they attempt to grasp its meaning (Field, 2008a;Tsui & Fullilove, 1998).…”
Section: Introductionmentioning
confidence: 99%